Perlindungan Hukum bagi UMKM terhadap Praktik Predatory Pricing pada E-commerce di Indonesia - N, Nadira; Mardjiono, H. R. Adianto (Media Hukum Indonesia (MHI), 2026)
Predatory pricing strategies in Indonesia’s e-commerce sector, particularly through TikTok Shop, have sparked significant debate regarding the sustainability of micro, small, and medium enterprises (MSMEs) as the backbone of the national economy. MSMEs employ more than 61% of the country’s workforce and provide vital employment opportunities, yet remain vulnerable to aggressive pricing tactics by large platforms due to limited capital, digital literacy, and market access. TikTok Shop’s aggressive measures such as deep discounts, subsidized free shipping, and shopping vouchers encourage consumer purchases even at a loss, thereby destabilizing market equilibrium, slowing MSME growth, and discouraging small business owners from investing. This object research to examine the law protections afforded to MSMEs against exploitative pricing practices by employing normative legal methodology and legislative analysis. The study concern on Article 20 of Law No. 5 of 1999 about Unfair Business Competition and Anti-Mnopoly Law, KPPU Regulation No. 6 of 2011 on the Guidelines for Article 20, Law No. 20 of 2008 on MSMEs. Findings reveal that while the regulatory framework provides a strong normative foundation, proving the element of intent (mens rea) among business actors remains a major challenge for enforcement. Strengthening the institutional foundation of KPPU and ensuring closer cross-sectoral policy coordination are essential to enhance protection for MSMEs and consumers in the digital marketplace.